Causal analysis for alarm flood reduction. Issue 7 (2016) - Rodrigo, Vicent; Chioua, Moncef; Hagglund, Tore; Hollender, Martin
Abstract: The introduction of distributed control systems and the high level of interconnectivity of modern process plants has caused alarm flooding to become one of the main problems in alarm management of process plants. A reduction of alarm flood periods contributes to a decrease in plant incidents. In this work, a combination of alarm log, process data and connectivity analysis is used to isolate consequence alarms originating from the same process abnormality and to provide a causal alarm suggestion. The effectiveness of the method is illustrated on an industrial case study of an ethylene plant, a typical example of a large-scale industrial system.